Biocontrol potential of mycogenic copper oxide nanoparticles against Alternaria brassicae - Gaba, Swati; Rai, Ashutosh Kumar; Varma, Ajit; Prasad, Ram; Goel, Arti (Frontiers in Chemistry, 2022)
The biological synthesis of nanoparticles using fungal cultures is a promising and novel tool in nano-biotechnology. The potential culture of Trichoderma asperellum (T. asperellum) has been used to synthesize copper oxide nanoparticles (CuO NPs) in the current study. The necrotrophic infection in Brassica species is caused due to a foliar pathogen Alternaria brassicae (A. brassicae). Mycogenic copper oxide nanoparticles (M-CuO NPs) were characterized by spectroscopic and microscopic techniques such as UV–visible spectrophotometry (UV–vis), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). The antifungal potential of CuO NPs was studied against A. brassicae. M-CuO NPs exhibited a surface plasmon resonance (SPR) at 303 nm, and XRD confirmed the crystalline phase of NPs. FTIR spectra confirmed the stretching of amide bonds, and the carbonyl bond indicated the presence of enzymes in T. asperellum filtrate. SEM and TEM confirmed the spherical shape of M-CuO NPs with an average size of 22 nm. Significant antifungal potential of M-CuO NPs was recorded, as it inhibited the growth of A. brassicae up to 92.9% and 80.3% in supplemented media with C-CuO NPs at 200 ppm dose. Mancozeb and propiconazole inhibited the radial growth up to 38.7% and 44.2%. SEM confirmed the morphological changes in hyphae and affected the sporulation pattern. TEM revealed hardly recognizable organelles, abnormal cytoplasmic distribution, and increased vacuolization, and light microscopy confirmed the conidia with reduced diameter and fewer septa after treatment with both types of NPs. Thus, M-CuO NPs served as a promising alternative to fungicides.